APLIKASI PENENTUAN STATUS BERAT DAN TINGGI BALITA - Nur Nafi’iyah; Mochammad Afif (STMIK YADIKA BANGIL, 2019)
Determining the condition of a healthy baby or toddler can be based on nutritional status and indicators. Some government steps in improving toddler nutrition in Indonesia are accurate and sustainable nutrition development. Various Indonesian government programs in improving toddler nutrition include the formulation of nutrition policies and guidance. To help the Indonesian government program in improving the nutrition of children under five, the researchers made an application to determine the status of toddlers from age to weight and age to height. Where to determine the nutritional status of children can use one of them, namely: WHO 2005 anthropometric standards set by the Minister of Health. How to determine using age category is calculated in full months, body length is used for children aged 0-24 months measured by supine, and height for children aged 24 months and above is measured by standing. The purpose of this study, which is to help mothers and midwives in determining the nutritional status of children based on body weight to age and height. The application uses the reference table for toddlers or ZSCORE nutritional status categories that have been determined by the Minister of Health. Kata kunci: heavy status, high status, zscore.